2006
DOI: 10.22358/jafs/66929/2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dried roots of <i>Astragalus membranaceus</i> in the diets of young growing pigs on growth performance and immune function

Abstract: The experiment was conducted to investigate the effect of Astragalus powder prepared by using different comminution techniques on growth performance and immune function of pigs. Duroc × Landrace × Yorkshire young growing pigs (n=90, female, 60 days of age, liveweight 21.88 ± 1.26 kg) were randomly allocated to three treatments. Each treatment had three replicates with ten pigs per pen. The basal diets were not supplemented or supplemented (5 g/kg) with 80 mesh Astragalus (180 μm), or micron Astragalus (6.32 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
2
9
1
1
Order By: Relevance
“…In this study, pigs fed HM supplementation diet had higher IgG and IgA concentrations compared with CON treatment at week 12, which is in agreement with Hu et al. (), who indicated that the supplementation of Astragalus membranaceus increased the IgA and IgG concentrations. Mao et al.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, pigs fed HM supplementation diet had higher IgG and IgA concentrations compared with CON treatment at week 12, which is in agreement with Hu et al. (), who indicated that the supplementation of Astragalus membranaceus increased the IgA and IgG concentrations. Mao et al.…”
Section: Discussionsupporting
confidence: 92%
“…The current results suggest that baizhu did improve growth performance and that this effect depended on the preparation technique. In our previous research we found that micronized Astragalus significantly increased the ADG of young growing pigs (Hu et al, 2006).…”
Section: Effect Of Baizhu On Pr-39 Mrna Expressionmentioning
confidence: 81%
“…Those results indicated that the medicinal efficiency of AMK is related to its effective ingredient. In our previous research we found that Astragalus membranaceus prepared with different comminution techniques has significantly different effects on immune function and growth performance in young growing pigs, which may be related to the bioavailability of the effective ingredients (Hu et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The improvement of cutaneous candidiasis following topical application of aqueous extract of Av may be related to the boosting of immune systems. The immunostimulating activity of Astragalus species has been subject of several studies (Kong et al, 2004;Hu et al, 2006). Twenty-eight patients with systemic lupus erythematosus had significantly decreased natural killer cell activity when compared to normal controls.…”
Section: Discussionmentioning
confidence: 99%